Draft Sixth Five Year Plan 1980-85 and Draft Annual Plan 1981-82 Volume I (Overview) Government of Assam - Planning Commission (Planning Commission, 1980)
This abnormal growth has not only inflated the size of the State’s total population, but has also caused other problems by disturbing its composition materially. The State has the proud privilege of being the traditional home of a large and rich variety of languages, religions, castes, tribes and cultures.
Government of Assam, Planning and Development Department